A new species of Leptodactylus (Anura: Leptodactylidae) from the state of Espirito Santo, Brazil, with remarks on the systematics of associated populations - de Padua Almeida, Antonio; Angulo, Ariadne (Zootaxa, 2006)
Adults and tadpoles of a new species of the genus Leptodactylus are described from southeastern Brazil. Leptodactylus thomei sp.nov. can be found amidst the leaf litter within cocoa plantations along the northern coastal region of the state of Espírito Santo. It can be distinguished from other species of the Leptodactylus marmoratus group by its advertisement call, which is described, together with agonistic calls, and compared to advertisement calls of other species of the group that occur in southern and southeastern Brazil. The systematics of associated populations is discussed.